2021
DOI: 10.3390/vaccines9101170
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Factors Influencing COVID-19 Vaccination Intentions: An Application of the Protection Motivation Theory Using a Probability Community Sample

Abstract: COVID-19 vaccines, as one of the effective ways of dealing with the COVID-19 pandemic, can lower COVID-19 risk and protect against severe disease and death; however, substantial individual differences in vaccination intentions have hindered the realization of a high vaccination rate among the public. To look for efficient strategies to promote vaccination, this study tested whether the protection motivation theory (PMT), a cognitive model based upon threat and coping appraisals, would account for the differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
(58 reference statements)
0
21
1
1
Order By: Relevance
“…Again, other unmeasured constructs may mediate this association. For example, threat and coping appraisals from protection motivation theory, such as perceived severity and vulnerability, and perceived efficacy of the booster vaccine, respectively, may have accounted for effect of vaccine hesitancy on intentions (see Tong et al, 2021 for an example). Similarly, the affective beliefs individuals hold with respect to their booster vaccination intentions such as fears or concerns about vaccine procedures themselves (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Again, other unmeasured constructs may mediate this association. For example, threat and coping appraisals from protection motivation theory, such as perceived severity and vulnerability, and perceived efficacy of the booster vaccine, respectively, may have accounted for effect of vaccine hesitancy on intentions (see Tong et al, 2021 for an example). Similarly, the affective beliefs individuals hold with respect to their booster vaccination intentions such as fears or concerns about vaccine procedures themselves (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…PMT has been applied to explain a wide range of health behaviours (for reviews, see Floyd et al, 2000 ; Milne et al, 2000 ; Norman et al, 2015 ) including intentions to receive a seasonal influenza vaccine ( Ling et al, 2019 ) and adherence to Covid-19 protection behaviours ( Scholz and Freund, 2021 ). PMT encompasses many of the beliefs associated with intended uptake of a Covid-19 vaccine identified in the Lin et al (2021) review and, since this review, a number of cross-sectional studies have used PMT to explain Covid-19 vaccination intentions ( Ansari-Moghaddam et al, 2021 ; Eberhardt and Ling, 2021 ; Huang et al, 2021 ; Tong et al, 2021 ) although, to date, no PMT studies have predicted subsequent uptake. For example, Eberhardt and Ling (2021) reported that PMT explained 68% of the variance in Covid-19 vaccination intentions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the predictors for COVID-19 vaccine uptake in the general population ( Al-Mansour et al, 2021 ; Al-Qerem and Jarab, 2021 ; Glampson et al, 2021 ; Kreps and Kriner, 2021 ; Lau et al, 2021 ; McCabe et al, 2021 ; Nguyen et al, 2021 ; Seboka et al, 2021 ; Tong et al, 2021 ; Wong et al, 2022 ; Yu et al, 2021 ). Furthermore, these studies investigated several demographic, health condition and lifestyle characteristics of the general population, such as gender, age, race/ethnicity educational level, living status, profession, income, perceived health status, chronic medical conditions, smoking status, perceived COVID-19 exposure, knowledge of COVID-19, contact with known/suspected case of COVID-19, sources of knowledge about COVID-19 vaccines, etc.…”
Section: Introductionmentioning
confidence: 99%